2020
DOI: 10.37107/jhas.140
|View full text |Cite
|
Sign up to set email alerts
|

Perception and Factors Influencing Junk Food Consumption among School Children of Pokhara

Abstract: Introduction: The main problem with junk foods is that they're low in satiation, that is, people don't feel as full when they eat them, which can lead to overeating. Another problem is that junk food tends to replace other more nutritious foods. In our diet over the time, urbanization and recent development in the foods industries have led to the notable increase in junk food production making them readily available, accessible and affordable. The main objective of this study was to understand the perception a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 7 publications
2
12
0
Order By: Relevance
“…This result is consistent with a study among Australian schoolchildren, which indicated that unhealthy snack food consumption declines with the students' increasing age and grades (Niven et al, 2015). However, a cross-sectional study conducted in Pokhara of Nepal showed that the average consumption of junk food increases as students' grade increases (Pahari and Baral, 2020).…”
Section: Discussionsupporting
confidence: 90%
“…This result is consistent with a study among Australian schoolchildren, which indicated that unhealthy snack food consumption declines with the students' increasing age and grades (Niven et al, 2015). However, a cross-sectional study conducted in Pokhara of Nepal showed that the average consumption of junk food increases as students' grade increases (Pahari and Baral, 2020).…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, 97.2 percent consumed pani-puri, 95.8 percent biscuits, 93 percent donuts, 92.3 percent chocolate, 65.5 percent ice cream and soft drinks and 18.3 percent consumed chapatti. In the same way another similar study presented that 15.5 percent of the respondents chose fast food, 27.7 percent of the respondents chose snacks, 8.6 percent of the respondents preferred soft drinks and 48.2 percent of the respondents chose chocolates (Pahari & Baral, 2020). The different contextual study shows similar results.…”
Section: Discussionsupporting
confidence: 62%
“…Likewise, 6.9 percent of the respondents consumed junk food because of its attractive advertisements, 5.6 percent of the respondents consumed junk food because of its convenience and 8.8 percent of the respondents consumed junk food because of its availability in restaurants (Khongrangjem et al, 2017). In another survey, 35 percent of respondents pointed out that the main causes for using junk food is not having time to cook at home, while 33.6 percent of respondents said that they preferred junk food because it tastes better than home cooked foods, 6.4 percent of respondents said that they ate junk food as per the wishes of their parents and the remaining 6.8 percent said that they ate junk food due to peer pressure (Pahari & Baral, 2020). Furthermore, one study also concluded that 90.1 percent of the respondents consumed junk food because it tasted good, 44.4 percent of the respondents consumed junk food because it could be prepared fast, 31.7 percent of the respondents consumed junk food because of peer influence, 29.6 percent of the respondents consumed it because nothing else was available, 15.5 percent of the respondents consumed it because of TV advertising (Sapkota & Neupane, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the study indicated that there was a statistical association between the gender of the students and the preferred choice of junk food while the findings of this study showed significant association of level of knowledge with gender and type of family of the respondents. Furthermore, advertisement was found to be one of the major influencing factors (13.6%) for junk food consumption among children while nearly half of the participants (42.2%) also found advertisement as the influencing factor in this study (Pahari & Baral, 2020).…”
Section: Discussionmentioning
confidence: 51%